Hesitancy to receive the novel coronavirus vaccine and potential influences on vaccination among a cohort of healthcare workers in the Democratic Republic of the Congo. Issue 34 (12th August 2022) - Barrall, Angelica L.; Hoff, Nicole A.; Nkamba, Dalau Mukadi; Musene, Kamy; Ida, Nicholas; Bratcher, Anna; Dzogang, Camille; Tangney, Sylvia; Beia, Michael; Nzaji, Michel Kabamba; Kampilu, David; Mbaka Onya, Gloire; et al.
Highlights: COVID-19 vaccine hesitancy was not static among a HCW cohort in the DRC over time. Vaccine hesitancy among the HCWs dramatically increased in mid-March 2021. Nearly a quarter of respondents reported vaccine hesitancy in late-August 2021. Patterns between reported influences on willingness to get vaccinated varied over time. Support for vaccine schedule adherence, apart from COVID-19, was consistently high. Abstract: Hesitancy to receive the COVID-19 vaccine among healthcare workers (HCWs) in low-resource settings, such as the Democratic Republic of the Congo (DRC), is a major global health challenge. This study identifies changes in willingness to receive vaccination among 588 HCWs in the DRC and reported influences on COVID-19 vaccination intentions. Up to 25 repeated measures were collected from participants between August 2020 to August 2021. Among the overall cohort, between August 2020 and mid-March 2021, the proportion of HCWs in each period of data collection reporting COVID-19 vaccine hesitancy ranged from 8.6% (95% CI: 5.97, 11.24) to 24.3% (95% CI: 20.12, 28.55). By early April 2021, the proportion reporting hesitancy more than doubled (52.0%; 95% CI: 46.22, 57.83). While hesitancy in the cohort began to decline by late-June 2021, 22.6% (95% CI: 18.05, 27.18) respondents indicated hesitancy in late-August 2021 which remains greater than the proportion of hesitancy at any time prior to early-March 2021. Patterns in reported influences on COVID-19 vaccination were varied with the proportion reporting some influences (e.g., no serious side effects, country of vaccine production) remaining stable throughout the year and other factors (e.g., recommendation of Ministry of Health, ease of vaccination) falling in popularity among respondents. Agreement that the national vaccination schedule should be followed apart from the COVID-19 vaccine remained high among respondents throughout the study period. This study shows that, among a cohort of HCWs in the DRC who have likely been influenced by regional, national, and global factors, COVID-19 vaccine hesitancy has fluctuated during the pandemic and should not be treated as a static factor. Additional research to determine which factors most influence HCWs' willingness to receive the COVID-19 vaccine offers opportunities to reduce vaccine hesitancy among this important population through tailored public health messaging.